IFN-γ enhances protective efficacy against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Yu, Ruying; Zhang, Weixiang; Yu, Penghui; Zhou, Jiancheng; Su, Jianguo; Yuan, Gailing (Frontiers in Immunology, 2024)
Abstract Nocardia seriolae (N. seriolae) adversely impacts a diverse range of fish species, exhibiting significant pathogenic characteristics that substantially impede the progress of aquaculture. N. seriolae infects fish with a long incubation period, and clinical symptoms are not obvious in the early stages. There is presently no viable and ecologically friendly approach to combat the spread of the disease effectively. According to reports, N. seriolae primarily targets macrophages in tissues after infecting fish and can proliferate massively, leading to the death of fish. IFN-γ is a critical molecule regulating macrophage activation, but little is known about its role in the N. seriolae prevention. In this study, the IFN-γ was first defined as largemouth bass (Micropterus salmoides) (MsIFN-γ), which has a highly conserved IFN-γ characteristic sequence through homology analysis. Trx-tagged recombinant fusion MsIFN-γ (rMsIFN-γ) proteins were obtained in Escherichia coli (E. coli) strain BL21 (DE3). In the inflammatory response of monocytes/macrophages activated by rMsIFN-γ, various cytokines were significantly increased. Interestingly, IL-1β and TNF-α increased by 183-fold and 12-fold after rMsIFN-γ stimulation. The rMsIFN-γ improved 42.1% survival compared with the control. The bacterial load in the liver, spleen and head kidney significantly declined. rMsIFN-γ was also shown to better induce increased expression of IL-1β, TNF-α, Hep-1, MHC I and MHC Ⅱ in head kidney, spleen and liver. The histopathological examination demonstrated the transformation of granuloma status from an early necrotic foci to fibrosis in the infected period. Unexpectedly, the development of granulomas was successfully slowed in the rMsIFN-γ group. In summary, this work paves the way for further research into IFN-γ of largemouth bass and identifies a potential therapeutic target for the prevention of N. seriolae.